ANALYSIS OF THE INFLUENCE OF BUYING INTEREST USING ONLINE TRAVELING APPLICATIONS IN INDONESIA - Perdinan Machelino Pardede; Hepy Hefri Ariyanto (Universitas Islam Lamongan, 2022)
Consumer decision making on online travel products through online applications continues to increase until now which is based on consumer trust and the risks taken, consumer satisfaction is also a major factor in making repurchase decisions in the future. This study aims to analyze travel relate behavior, online reviews, personal traits, perceived risk, online satisfaction, trust, product quality, how to influence purchase intention in people in Indonesia. In this study, an online survey was conducted to 410 respondents and the results showed that, online review, perceived risk, trust, product quality had a significant effect on purchase intention. On the other hand, travel relate behavior, personal traits, and online satisfaction have no significant effect on purchase intention.Keywords – Travel Relate Behaviour, Online Review, Personal Traits, Perceived Risk, Online Satisfaction, Trust, Product quality, Purchase intention.